Adherence to the Mediterranean Diet in Relation to Gastric Cancer in Afghanistan - Amiry, Freshta; Mousavi, Seyed Mohammad; Barekzai, Ahmad Mujtaba; Esmaillzadeh, Ahmad (Frontiers in Nutrition, 2022)
Background Despite the adherence to the Mediterranean dietary pattern (MD) being associated with a reduced risk of several cancers, there is no report about the highly prevalent diet-disease associations in Afghanistan, particularly about gastric cancer (GC). Objective The aim of this study was to investigate the association between MD and GC in Afghanistan. Methods This hospital-based case-control study was carried out on a total number of 270 subjects (90 cases and 180 controls) aged between 20 and 75 years. Using the convenience-sampling method, cases and controls were selected. Cases were patients with GC whose condition was pathologically confirmed. The controls were apparently healthy people who were matched with cases in terms of age (±5 years) and sex. Assessment of dietary intake was done using a pre-tested food frequency questionnaire, designed specifically for Afghanistan. Adherence to the MD pattern was done based on the scores suggested in earlier studies. Results Out of 270 studied subjects, 73% were men. We found that subjects in the highest tertile of MD score had 52% decreased odds of GC (OR: 0.48; 95% CI: 0.24–0.98, P-trend = 0.05) compared with those in the lowest tertile. After considering potential environmental factors, age, and sex, the observed association disappeared (OR: 0.43; 95% CI: 0.13–1.38, P-trend = 0.41). After further adjustment for BMI in the last model, we found that participants with the highest MD score were 83% less likely to have GC than those in the lowest tertile (OR: 0.17; 95% CI: 0.03–0.80, P-trend = 0.14). Conclusion We found that greater adherence to MD might be associated with a lower odds of GC.